(untitled) (Itinera, 2020)
James Turrell’s installation Sight Unseen can provide useful elements concerning the philosophical discourse on colors. The artwork shows how the physical nature of the light allows the environmental diffusion of colors. Meant as character of light itself, the color organizes and disposes the perception of the space explored by spectators. I assume an ecological aesthetic perspective to understand the perceptual phenomena that affect the senses of the spectators’ living body and broaden the current physicalist and representationalist models emerged within theories of color.